1975
DOI: 10.1021/jm00245a014
|View full text |Cite
|
Sign up to set email alerts
|

Antiallergic activity of 2-phenyl-8-azapurin-6-ones

Abstract: The synthesis and antiallergic activity in the rat passive cutaneous anaphylactic reaction of a series of 2-phenyl-8-azapurin-6-ones are described. Early in the investigation, a linear free-energy equation was established in which the activity was related to the size and hydrogen bonding capacity of the ortho substituent in the phenyl ring. This relationship was used to provide guidance and limits for subsequent work leading to 2-o-propoxyphenyl-8-azapurin-6-one which is 40 times more potent than disodium crom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…Comparison with 1 H NMR spectra (Table 3) of other pairs of ortho and para isomers for which intramolecular hydrogen-bonded structures were not possible (10b and 10n, and also 10e and 10q) strengthened this interpretation: the NϪH signals were always observed in the δ ϭ 7.8Ϫ8.7 range in CDCl 3 and in the δ ϭ 11.4Ϫ11.8 range in DMSO for both ortho and para isomers, respectively. The situation observed is not new, and is reminiscent of the findings of Wooldridge et al, [19] who reported on the occurrence of strong intramolecular hydrogen bonding between an ortho-alkoxy substituent and the N(1)ϪH proton of a series of 2-aryl-8-azopurin-6-ones. As a matter of fact, the proton of a pyrimidone ring amide group gives an intramolecular hydrogen bond with the oxygen atom of the alkoxy group.…”
Section: The Origin Of the Peculiar Behaviour Of O-methoxy Derivativesupporting
confidence: 56%
“…Comparison with 1 H NMR spectra (Table 3) of other pairs of ortho and para isomers for which intramolecular hydrogen-bonded structures were not possible (10b and 10n, and also 10e and 10q) strengthened this interpretation: the NϪH signals were always observed in the δ ϭ 7.8Ϫ8.7 range in CDCl 3 and in the δ ϭ 11.4Ϫ11.8 range in DMSO for both ortho and para isomers, respectively. The situation observed is not new, and is reminiscent of the findings of Wooldridge et al, [19] who reported on the occurrence of strong intramolecular hydrogen bonding between an ortho-alkoxy substituent and the N(1)ϪH proton of a series of 2-aryl-8-azopurin-6-ones. As a matter of fact, the proton of a pyrimidone ring amide group gives an intramolecular hydrogen bond with the oxygen atom of the alkoxy group.…”
Section: The Origin Of the Peculiar Behaviour Of O-methoxy Derivativesupporting
confidence: 56%
“…Chemically, approaches towards amidines lay on the reduction of amidoximes (Scheme 5), either via catalytic hydrogenation with palladium in charcoal in the presence of acetic acid [25], or reduction with Zn in acetic acid [26] or transition metal catalysis in general [27][28][29]. Scheme 5.…”
Section: Ii4 Synthesis Of Amidinesmentioning
confidence: 99%
“…It has been suggested that the substituent effect may be attributable to intramolecular hydrogen bonding between the alkoxy oxygen and the proton of the pyrimidine ring NH group (Broughton et al, 1975). Recently, much attention has been devoted to dihydropyrimidine derivatives because of their significant therapeutic and medicinal properties (Kappe, 1993;Kappe et al, 1997).…”
Section: Commentmentioning
confidence: 99%